EFEKTIVITAS SLOW STROKE BACK MASSAGE TERHADAP TEKANAN DARAH DAN KUALITAS TIDUR PENDERITA HIPERTENSI - Imelda Wahyu Hermawan; Felicia Risca Ryandini; Suksi Riani (Medical Journal of Nusantara, 2024)
Known as hypertension, or high blood pressure, is a non-communicable disease (NCD). Preliminary study data from Dr. Kariadi Semarang Central Public Hospital indicated 561 patients with hypertension over the last three years (2021–2023). Hypertension symptoms often resemble those of other diseases and can vary among individuals, including fatigue, palpitations, increased blood pressure, nosebleeds, headaches, and nocturia, which can disrupt sleep quality. One of the non-pharmacological effort to prevent hypertension is slow-stroke back massage, This study aimed to determine the effect of slow-stroke back massage on blood pressure and sleep quality in hypertension sufferers. The research design employed a quasi-experimental method with a one-group pretest-posttest approach, involving 42 respondents selected through purposive sampling. The results demonstrated that slow-stroke back massage effectively reduced systolic blood pressure (p-value = 0.00) and improved sleep quality scores (p-value = 0.00). Slow-stroke back massage can enhance relaxation and increase parasympathetic nerve activity, thereby reducing the heart's workload. This study recommends that nurses apply slow-stroke back massage therapy in hospitals to help control blood pressure and improve the sleep quality of hypertension sufferers.